Do Roma Communities Only Get to Deal with Suffering? “Roma Heroes II. Five European Dramas Kindle Edition” by Independent Theater Hungary Rodrigó Balogh (Author), M. Drăgan-Z. Moldovan-L. Ceterchi-M. Lukács (Authors), Richard R. O’Neill (Author), J. Nikolić-R. R. Seidović (Authors), Igor Krikunov (Author), Rodrigó Balogh (Author) Format: Kindle Edition. September 28, 2021. - BÖJTHE, Pál (Studia Universitatis Babeș-Bolyai Dramatica, 2022)
This volume is a sequel to the first Roma Heroes anthology of monodramas and contains stories from five different countries. The chamber dramas bring us to Germany, Hungary, Romania, Ukraine, and into the virtual theatre world: a play created online was also included in the book.